Evaluation of high-volume fly-ash cementitious binders incorporating nanosilica as eco-friendly sustainable concrete repair materials - Huseien G.F.; Tang W.; Yu Y.; Wong L.S.; Mirza J.; Dong K.; Gu X. (Elsevier Ltd, 2025)
Nowadays, the use of environmentally friendly, long-lasting building materials with minimal energy and carbon dioxide emissions are highly recommended. Some of these materials can be made from industrial and agricultural wastes. By replacing ordinary Portland cement (OPC) with large volume of fly ash waste (FA), environmental issues associated with landfill disposal and cement manufacture can be mitigated. Nonetheless, using a high amount of FA (up to 50 %) to replace cement resulted in poor strength performance, particularly during early age. This experimental study created an increased strength cement mortar containing a high volume of FA (60 %) and bottle glass waste nanoparticles (BGWNPs). In this experiment BGWNPs were prepared and 2, 4, 6, 8 and 10 vol% of them were used as a replacement of OPC-FA binder. According to the results, by adding 0?6 % of BGWNPs to a high-volume FA matrix considerably increased the bond strength (from 12.5 % to 39.1 %). On the other hand, the findings revealed that the addition of nanoparticles (up to 6 %) caused a modest reduction in strength values. Other engineering and microstructure properties showed a similar pattern. The matrix with 6 % BGWNPs displayed the best performance when compared to other levels. The results also showed that replacing OPC by high volume FA incorporating BGWNPs significantly improved the durability of proposed mortar, such as reduction in drying shrinkage and increased acid attack and abrasion resistance. Related to the environment benefits, the proposed mortars contributed in a reduction of carbon dioxide emission, energy consumption and cost of binder by 61.9 %, 54.3 % and 50.6 % compared to OPC, respectively. To conclude, the use of BGWNPs make it possible to produce high volumes of FA-based cement mortars with acceptable mechanical and durable properties for concrete repair applications in the construction industry. Additionally, sustainability can be attained by lowering pollution, recycling waste, and finding solutions to landfill problems. ? 2024 Elsevier Ltd